On Inclusion Relations between Some Sequence Spaces - Colak, R.; Bektas, C. A.; Altinok, H.; Ercan, S. (Hindawi Ltd, 2016)
We determine the relations between the classes (S) over cap (lambda) of almost lambda-statistically convergent sequences and the relations between the classes [(V) over cap, lambda] of strongly almost (V, lambda)-summable sequences for various sequences A, 11 in the class A. Furthermore we also give the relations between the classes S5 of almost lambda-statistically convergent sequences and the classes [(V) over cap, lambda] of strongly almost (V, lambda)-summable sequences for various sequences lambda,mu is an element of A.